2021
DOI: 10.1126/science.abi6060
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Reintroduction of the archaic variant of NOVA1 in cortical organoids alters neurodevelopment”

Abstract: Trujillo et al. (Research Articles, 12 February 2021 conclude that the reintroduction of an ancestral amino acid substitution in the protein NOVA1 drastically alters the development of brain organoids. We show that cell lines used by the authors carry heterozygous deletions of the target DNA sequence, providing another plausible explanation for the effects observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…For example, human organoids with the ancestral amino acid variant of splicing regulator NOVA1 (isoleucine instead of valine) were reported to be smaller and have more cell death, to have a more uneven external surface, and to have gene expression differences in synaptic and glutamatergic markers compared to those with the modern human variant ( Trujillo et al, 2021 ). However, it has been questioned whether these phenotypes were really due to the single amino acid substitution in NOVA1 ( Herai et al, 2021 ; Maricic et al, 2021 ).…”
Section: Evolutionary Aspects—are There Differences In Key Players Of...mentioning
confidence: 99%
“…For example, human organoids with the ancestral amino acid variant of splicing regulator NOVA1 (isoleucine instead of valine) were reported to be smaller and have more cell death, to have a more uneven external surface, and to have gene expression differences in synaptic and glutamatergic markers compared to those with the modern human variant ( Trujillo et al, 2021 ). However, it has been questioned whether these phenotypes were really due to the single amino acid substitution in NOVA1 ( Herai et al, 2021 ; Maricic et al, 2021 ).…”
Section: Evolutionary Aspects—are There Differences In Key Players Of...mentioning
confidence: 99%
“…These events are likely detrimental and can lead to haploinsufficiency or to the production of a dysfunctional protein. For example, in a recent study, a CRISPR/Cas9-edited clone was falsely identified as homozygous, while, in fact, a small deletion prevented proper sequencing of targeted region (Herai et al, 2021;Maricic et al, 2021;Trujillo et al, 2021). Moreover, the genetic consequences of copy-neutral LOH, which we identified in another falsely corrected clone, are not limited to the target locus, as LOH can uncover recessive alleles and elicit long-range transcriptional consequences.…”
Section: Discussionmentioning
confidence: 80%
“…A concern when performing genome editing is unintended effects that may affect the target sites, notably deletions ( 43 , 48 ) that may not be detected when the target site is sequenced ( 49 ). To exclude this, we determined the copy number of the locus after editing and verified that polymorphic positions up- and downstream of each site remained heterozygous after editing.…”
Section: Discussionmentioning
confidence: 99%